Determinants of success in venture capital investments: evidence from Brazil. Issue 3 (3rd July 2017) - De Carvalho, Antonio Gledson; Gallucci-Netto, Humberto; Siqueira, Eduardo M. R.
Abstract: We investigate the determinants of the success of private equity/venture capital funds. We focus specially on a Brazilian idiosyncrasy: the participation of limited partners in the investment process through investment committees (ICs) staffed with their representatives. In principle, ICs could substitute for the ex post screening that creditors do in levered buyouts. We find that funds with ICs underperform other funds, suggesting that ICs are not a good alternative for creditors screening. We also find that funds managed by bank affiliates underperform those managed by independent organizations. Finally, retention of equity control on portfolio companies affects positively their success.